REGULATION OF MHC I MOLECULES IN GLIOBLASTOMA CELLS AND THE SENSITIZING OF NK CELLS - Burster, Timo; Gärtner, Fabian; Bulach, Christiane; Zhanapiya, Anuar; Gihring, Adrian; Knippschild, Uwe (Pharmaceuticals, 2021)
Immunotherapy has been established as an important area in the therapy of malignant diseases. Immunogenicity sufficient for immune recognition and subsequent elimination can be bypassed by tumors through altered and/or reduced expression levels of major histocompatibility complex class I (MHC I) molecules. Natural killer (NK) cells can eliminate tumor cells in a MHC I antigen presentation-independent manner by an array of activating and inhibitory receptors, which are promising candidates for immunotherapy. Here we summarize the latest findings in recognizing and regulating MHC I molecules that affect NK cell surveillance of glioblastoma cells
Keywords: Type of access: Open Access; immunotherapy; cathepsin G; MHC; NK cells; proteases